5w+41=3(w+9)

Simple and best practice solution for 5w+41=3(w+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w+41=3(w+9) equation:


Simplifying
5w + 41 = 3(w + 9)

Reorder the terms:
41 + 5w = 3(w + 9)

Reorder the terms:
41 + 5w = 3(9 + w)
41 + 5w = (9 * 3 + w * 3)
41 + 5w = (27 + 3w)

Solving
41 + 5w = 27 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
41 + 5w + -3w = 27 + 3w + -3w

Combine like terms: 5w + -3w = 2w
41 + 2w = 27 + 3w + -3w

Combine like terms: 3w + -3w = 0
41 + 2w = 27 + 0
41 + 2w = 27

Add '-41' to each side of the equation.
41 + -41 + 2w = 27 + -41

Combine like terms: 41 + -41 = 0
0 + 2w = 27 + -41
2w = 27 + -41

Combine like terms: 27 + -41 = -14
2w = -14

Divide each side by '2'.
w = -7

Simplifying
w = -7

See similar equations:

| 0.333333(x+3)+0.1666666(x-6)=x+3 | | (4x+1500)-(2x+1800)=0 | | -4/3x^2-19/18x-19/36=0 | | 2y+3=3(7+7) | | G+2(3+g)=4(g+1) | | 2=400/x | | (x+5y)dy=-(2x+3y)dx | | 7=5(x+5)-7x | | onethird(x+3)+onesixth(x-6)=x+3 | | 5xa-7a^2=2a^2+2ax | | -6x-3(7x-26)=-111 | | 4a-2a+11=6a-13 | | 9w+5= | | 5ax-7a^2=2a^2+2ax | | 8(-7+8v)=200 | | 9w-5= | | 1p-15=13-6p | | 10p+6=-18-2p | | 29=4x-5 | | 2x^2=-2 | | -9v-6+7v=16 | | (2x+1500)-(4x-1800)=0 | | 5x-13=11+3x | | -18-[3(x+2)+4]=21-[6(-2x-2)+1] | | (x+5y)dy+(2x+3y)dx=0 | | -(5/12)y=25 | | 16+3s-2s=24+2s | | xxxx=69 | | 3x^2+36x+96= | | x.x.x.x=69 | | 5x-6(2x)=14 | | -5m+2+8m=2m |

Equations solver categories